Multitasking in Knowledge Intensive Business Services - Inese Suija-Markova; Liene Briede; Elīna Gaile-Sarkane; Iveta Ozoliņa-Ozola (Ital Publication, 2020)
The objectives of this study were two-fold. First, to analyze multitasking activities in Knowledge Intensive Business Services (KIBS) and the employees’ perception of multitasking effects on individual and organizational performance. Second, to explore associations between the perception of multitasking and individual Time Management Orientation (TMO). The research study employed an online survey methodology. The questionnaire contained 56 questions organised in four groups. Methods of relationship analysis and regression analysis were applied to get answers to the research questions. The study indicated that the employees of surveyed KIBS were strongly engaged in multitasking activities in their workplaces. The informants estimated that on average they worked on nine different tasks per day. Additionally, their working days were filled with interruptions, caused either by external factors or self-interruptions. The majority of respondents also admitted that the ability to multitask was considered their job requirement, thus supporting the findings of other studies that KIBS do prefer multitasking employees. The effects of multitasking on individual and organizational performance were perceived ambiguously by the respondents. Meanwhile, the majority of respondents (above 70%), regardless of the level of polychronicity, admitted that they were able to make good decisions and concentrate better when they worked on one task at a time. The data analysis confirmed the findings reported earlier that individuals with more polychronic TMO did perceive multitasking as having more positive than negative effects both at the individual and organisational levels. Human multitasking has been widely researched in such fields as medicine, command and control, aviation, information technologies, but there is little detailed empirical evidence on multitasking in KIBS such as management consulting, research and development, architecture, engineering services, design, and advertising. Our research provides a fresh view on the human aspects of KIBS companies which can be of help in addressing the related managerial issues. The setting of the optimal number of tasks, task allocation considering employees’ individual differences, designing of workflows require further research as this may give the KIBS company managers guidelines and tools for organizing productive multitasking towards enhanced work efficiency and effectiveness and employees’ well-being.